Introduction, Spread, and Establishment of West Nile Virus in the Americas. Issue 6 (24th September 2019) - Kramer, Laura D; Ciota, Alexander T; Kilpatrick, A Marm
Abstract: The introduction of West Nile virus (WNV) to North America in 1999 and its subsequent rapid spread across the Americas demonstrated the potential impact of arboviral introductions to new regions, and this was reinforced by the subsequent introductions of chikungunya and Zika viruses. Extensive studies of host–pathogen–vector–environment interactions over the past two decades have illuminated many aspects of the ecology and evolution of WNV and other arboviruses, including the potential for pathogen adaptation to hosts and vectors, the influence of climate, land use and host immunity on transmission ecology, and the difficulty in preventing the establishment of a zoonotic pathogen with abundant wildlife reservoirs. Here, we focus on outstanding questions concerning the introduction, spread, and establishment of WNV in the Americas, and what it can teach us about the future of arboviral introductions. Key gaps in our knowledge include the following: viral adaptation and coevolution of hosts, vectors and the virus; the mechanisms and species involved in the large-scale spatial spread of WNV; how weather modulates WNV transmission; the drivers of large-scale variation in enzootic transmission; the ecology of WNV transmission in Latin America; and the relative roles of each component of host–virus–vector interactions in spatial and temporal variation in WNV transmission. Integrative studies that examine multiple factors and mechanisms simultaneously are needed to advance our knowledge of mechanisms driving transmission.